2015
DOI: 10.3390/polym7030390
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dynamical Properties of Polyethylene/Graphene Nanocomposites through Molecular Dynamics Simulations

Abstract: Detailed atomistic (united atoms) molecular dynamics simulations of several graphene based polymer (polyethylene, PE) nanocomposite systems have been performed. Systems with graphene sheets of different sizes have been simulated at the same graphene concentration (~3%). In addition, a periodic graphene layer ("infinite sheet") has been studied. Results concerning structural and dynamical properties of PE chains are presented for the various systems and compared to data from a corresponding bulk system. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 32 publications
5
63
1
Order By: Relevance
“…Polymer nanocomposites have shown enormous potential to significantly enhance the polymers properties by using nano‐scale fillers . Graphene has recently become one of the most promising nanofillers for polymer nanocomposites because of its extraordinary mechanical, thermal and electrical properties . Graphene is a sp 2 ‐hybridized carbon layer with an atomic thickness, consisting of honeycomb‐like assembly of carbon atoms .…”
Section: Introductionmentioning
confidence: 99%
“…Polymer nanocomposites have shown enormous potential to significantly enhance the polymers properties by using nano‐scale fillers . Graphene has recently become one of the most promising nanofillers for polymer nanocomposites because of its extraordinary mechanical, thermal and electrical properties . Graphene is a sp 2 ‐hybridized carbon layer with an atomic thickness, consisting of honeycomb‐like assembly of carbon atoms .…”
Section: Introductionmentioning
confidence: 99%
“…However, R g of both PP and PVA is slightly larger in the first layer of PP/G and PVA/G, as compared the bulk values. Note that it has been shown that polymers exhibit either a similar or slightly higher values of R g very close to the attractive nanofillers . Therefore, drawing any conclusions about the differences between G‐based and GO‐based systems (only) based on these data is rather misleading.…”
Section: Resultsmentioning
confidence: 97%
“…Note that it has been shown that polymers exhibit either a similar or slightly higher values of R g very close to the attrac tive nanofillers. [33,34] Therefore, drawing any conclusions about the differences between Gbased and GObased systems (only) based on these data is rather misleading. However, bringing this result together with the density profile ( Figure 3) will emphasize on the higher packing of polymer chains in the vicinity of G rather than GO regard less of the nature of the polymer chain.…”
Section: Structural Analysismentioning
confidence: 99%
“…The same research group also performed these activities by taking into consideration the graphene and PE nanocomposite system. 217 Other Polymers-Based Graphene Nanocomposites Nayebi and Zaminpayma 88 computed the mechanical properties of graphene-polythiophene (PT) nanocomposites by altering, graphene weight percentages, graphene structure, and temperature of the simulation box. The improvements in mechanical properties predicted were associated with the increase in graphene weight fraction that also reflects a higher interfacial strength.…”
Section: Poly Methyl Methacrylate-based Graphene Nanocompositesmentioning
confidence: 99%